Influences of Religiosity, Capital Market Knowledge, and Information Technology on Sharia Investment Interest in Central Java, Indonesia - Alfian, Ahmad Hijri; Ramdhani, Muhammad Iqbal; Nugrahini, Dian Essa (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
A responsible government must establish stable economic conditions that foster societal well-being and expedite national prosperity. A strategic approach to achieving this is through the promotion and development of investment activities at district, city, and provincial levels. This research aims to investigate the factors influencing interest in sharia investment, with a particular focus on religiosity as a moderating variable. Utilizing primary data gathered through questionnaires from investors in Central Java Province, the study employs SEM-PLS analysis to assess the responses. The findings reveal that both knowledge of the sharia capital market and advancements in information technology positively impact interest in sharia investment. However, religiosity does not significantly moderate the effects of these two factors. Notably, the study identifies that religiosity directly influences interest in sharia investment. Policy implications suggest that in Central Java, interest in sharia investment is predominantly driven by knowledge and information technology; thus, further detailed information on sharia-compliant investment products is needed to align with investor interests.